Genetic Rearrangements of the Regions Adjacent to Genes Encoding Heat-Labile Enterotoxins (eltAB) of Enterotoxigenic Escherichia coli Strains - Schlör, Stefan (American Society for Microbiology, 2000)
One of the most common bacterially mediated diarrheal infections is caused by enterotoxigenic Escherichia coli (ETEC) strains. ETEC-derived plasmids are responsible for the distribution of the genes encoding the main toxins, namely, the heat-labile and heat-stable enterotoxins. The origins and transfer modes (intra- or interplasmid) of the toxin-encoding genes have not been characterized in detail. In this study, we investigated the DNA regions located near the heat-labile enterotoxin-encoding genes (eltAB) of several clinical isolates. It was found that the eltAB region is flanked by conserved 236- and 280-bp regions, followed by highly variable DNA sequences which consist mainly of partial insertion sequence (IS) elements. Furthermore, we demonstrated that rearrangements of the eltAB region of one particular isolate, which harbors an IS91R sequence next to eltAB, could be produced by a recA-independent but IS91 sequence-dependent mechanism. Possible mechanisms of dissemination of IS element-associated enterotoxin-encoding genes are discussed.